# SOLUTION: if f(x)=2x-3and g(x)=x^2+1 fog(-1) (gof) (4)I thank you in advanced please help me here .and with this onefind (f-g) (x) f(x) =x^2 -2x-24 and g(x)=x^2 -x-30

Algebra ->  Algebra  -> Functions -> SOLUTION: if f(x)=2x-3and g(x)=x^2+1 fog(-1) (gof) (4)I thank you in advanced please help me here .and with this onefind (f-g) (x) f(x) =x^2 -2x-24 and g(x)=x^2 -x-30       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Functions, Domain, NOT graphing Solvers Lessons Answers archive Quiz In Depth

 Question 287931: if f(x)=2x-3and g(x)=x^2+1 fog(-1) (gof) (4)I thank you in advanced please help me here .and with this onefind (f-g) (x) f(x) =x^2 -2x-24 and g(x)=x^2 -x-30 Answer by stanbon(57219)   (Show Source): You can put this solution on YOUR website!If f(x)=2x-3 and g(x)=x^2+1 fog(-1) (gof)(4) --- fog(-1) Step 1: find g(-1) = (-1)^2+1 = 1+1 = 2 So, f[g(-1)] = f(2) Step 2: find f(2) = 2(2)-3 = (4-3) = 1 ================================================== find (f-g) (x) f(x) =x^2 -2x-24 and g(x)=x^2 -x-30 (f-g)x = f(x)-g(x) Step 1: subtract g(x) from f(x) = (x^2-2x-24) - (x^2-x-30) Sept 2: simplify = -2x+x -24+30 = -x + 6 ============== Cheers, Stan H. ==============